"Falling off the wagon": older adults' experiences of living with frailty in rural arctic communities. Issue 1 (1st January 2021) - Bjerkmo, Lena; Helgesen, Ann Karin; Larsen, Toril Agnete; Blix, Bodil H.
ABSTRACT: Most populations around the world are ageing. The proportion of older adults in the population is larger and is growing more rapidly in rural communities than in urban areas. Longevity increases the risk of frailty. Our aim was to explore how single-living frail older adults experience living with frailty in everyday life in rural Arctic areas. Over eight months, we conducted a series of three interviews with eight older adults identified as frail by home care services in two rural municipalities in northern Norway. We conducted a thematic analysis. We generated three themes. Frailty as a dynamic phenomenon indicated that the participants' experiences of frailty varied over time. Frailty as part of old age referred to the findings that many participants tried to adapt to the changing circumstances, while others found it more challenging to accept the experienced limitations. Frailty in a rural Arctic context concerned the findings that the rural Arctic environment affected the participants' experiences of frailty due to its long, snowy winters; long distances between communities and municipal centres; and out-migration. Our results demonstrate that frailty is a consequence of the interplay between ageing persons and their physical and social environments.